Trademark Registration as Legal Protection for Small Industry of Batik Sragen - Saputro, Triyono Adi (Budapest International Research and Critics University, 2021)
Small industry is a pillar of the economy for a region or a nation, its role is very vital in contributing to the per capita income of a region. Attendance is very helpful for the government in carrying out the program launched in terms of poverty alleviation and unemployment reduction. Small batik industry in Sragen is the prima donna product that has been favored so far with the hope of being able to support the regional economy of Sragen. It is undeniable that the existence of the batik industry has been able to last for many years and support the regional economy of Sragen Regency. But the fame has not been able to cover various outside markets due to the absence of business legality for the batik product. The lack of legal awareness of business actors, low information about trademarks, limited human resources and the role of local governments have not been maximized all this time. Therefore, it is necessary to conduct a direct analysis to the field using empirical research methods which combine data on results in the field and based on applicable laws and regulations. The results show that there are still many batik products that have not registered their trademarks with a background of lack of legal awareness of business actors so that it is necessary to provide socialization and direct guidance in the regions in order to assist the registration process of legal protection through trademarks.